Design, synthesis and neuroprotective activity of compound derived from Gastrodia elata Blume and borneol - Zhi, Lijuan; Li, Huan; Shi, Baimei; Yu, Tao; Jia, Xiaoni; Zhang, Hui (Frontiers in Pharmacology, 2024)
Traditional Chinese medicine Gastrodia elata Blume (GEB) possesses properties that soothe the liver and dispel wind. Its constituents exhibit numerous pharmacological properties, including neuroprotective effects, analgesic properties for headache relief, memory enhancement, and others. Borneol enhances drug absorption by traversing the blood-brain barrier, thereby improving its bioavailability and therapeutic efficacy. This paper adopts the strategy of "compound Chinese medicine molecular chemistry" to integrate and fuse the effective substances of compound Chinese medicines, aiming to design innovative drug molecules and contribute to the beneficial exploration of compound Chinese medicine modernization. We designed and synthesized compounds TB-1 to TB-16. Following the evaluation of their safety, TB-1, TB-2, TB-12, and TB-16 were selected for further investigation of their neuroprotective properties. The compound designed in this study exhibits a dose-dependent protective effect on glutamate-damaged PC12 cells. Further network pharmacology and molecular docking analyses indicate that TB-2 possesses a potential therapeutic effect against cerebral ischemia, and its possible targets were SRC, MAPK1 and KDR.